A standard numbering scheme for class C β-lactamases - Mack, Andrew R. (2019)
Unlike for classes A and B, a standardized amino acid numbering scheme has not been proposed for the class C (AmpC) β-lactamases, which complicates communication in the field. Here, we propose a scheme developed through a collaborative approach that considers both sequence and structure, preserves traditional numbering of catalytically important residues (Ser64, Lys67, Tyr150, and Lys315), is adaptable to new variants or enzymes yet to be discovered and includes a variation for genetic and epidemiological applications.